2015
DOI: 10.1002/ajhb.22819
|View full text |Cite
|
Sign up to set email alerts
|

Residential context, institutional alloparental care, and child growth in Jamaica

Abstract: Younger children who lived with family members had better growth measurements than their peers living in institutional settings. However, improved growth measures for children living in one home were correlated to nonconventional counseling practices, and nutritional policies that mirror some aspects of familial care. Am. J. Hum. Biol. 28:493-502, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…In our study, health-related behavioral problems and a higher incidence of chronic disease were found in adolescents not living with families, which is consistent with previous studies [ 42 , 43 ]. For example, one study showed that young children who lived with family members had better growth measurements (a long-term health indicator) than their peers living in institutional settings [ 44 ]; students living at home practised more sports and more frequently consumed raw and cooked vegetables, fish, meat and poultry, fresh fruit, eggs, bread/cereals, and hence were in better health conditions [ 45 ]. Conversely, students living away from home consumed more packaged/ready food, beer and spirits, milk and chips.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, health-related behavioral problems and a higher incidence of chronic disease were found in adolescents not living with families, which is consistent with previous studies [ 42 , 43 ]. For example, one study showed that young children who lived with family members had better growth measurements (a long-term health indicator) than their peers living in institutional settings [ 44 ]; students living at home practised more sports and more frequently consumed raw and cooked vegetables, fish, meat and poultry, fresh fruit, eggs, bread/cereals, and hence were in better health conditions [ 45 ]. Conversely, students living away from home consumed more packaged/ready food, beer and spirits, milk and chips.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies of WEIRD populations have implicated poor attachment and neglect to a range of downstream issues, including but not limited to, disordered eating, impaired language development, poor emotional regulation and behavioral issues (Brumariu et al, 2012; van IJzendoorn et al, 1995; Ward et al, 2000). Evidence also supports the relationship between attentive caretaking and child physical growth (Black et al, 1994; Fuemmeler et al, 2012; Robin G Nelson, 2016). These findings suggest that at its core, there are some behaviors that must be present to support child thriving.…”
Section: Context Specific Norms and Variancementioning
confidence: 86%
“…Environmental context and resource availability may also affect the allocation of alloparental care (Martin et al, 2020). Additionally, research on Caribbean families highlights that not all alloparental care is equally beneficial (Flinn & Leone, 2009; Robin G Nelson, 2016). This flexibility in choice of alloparents and the utility of their care has lead Bogin and colleagues (Bogin et al, 2014) to argue that cooperative breeding is a misnomer for this observed human behavior.…”
Section: Theorizing Caretaking In Evolutionary Anthropologymentioning
confidence: 99%
“…Biological anthropologists are experts at teasing apart the complexities of biocultural interactions that inform what it is to be human, examining how broad‐ranging factors such as market acculturation (Godoy et al, 2005; Liebert et al, 2013), parenting strategies (McKenna et al, 2007; Nelson, 2016), or socially constructed categories of race (Dressler & Bindon, 2000; Gravlee, 2009) relate to physiology including growth and development, immune function, and endocrinology. Yet we have not fully engaged with cutting‐edge understandings of variation in gender, sex, and sexuality.…”
Section: Introductionmentioning
confidence: 99%